2017
DOI: 10.14407/jrpr.2017.42.3.154
|View full text |Cite
|
Sign up to set email alerts
|

Validation of MCNPX with Experimental Results of Mass Attenuation Coefficients for Cement, Gypsum and Mixture

Abstract: Background: Shielding properties of compound or mixture is presented in terms of mass attenuation coefficients using Monte Carlo simulation. Mass attenuation coefficients of cement, gypsum and the mixture of gypsum and PbCO3 has been investigated using monte carlo MCNPX. Materials and Methods: The mass attenuation coefficients of cement, gypsum and the mixture of gypsum and PbCO3 were calculated for photon energies 365.5, 661.6, 1,173.2, and 1,332.5 keV energies. Results and Discussion: The simulated values of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 10 publications
0
12
0
Order By: Relevance
“…Mass attenuation coefficient of an element is found to be constant at a particular photon energy, whereas mass attenuation coefficient of a compound or mixture depends upon composition of elements. The linear attenuation coefficient, half-value layer thickness, tenth-value layer thickness and effective atomic number are derived parameters from mass attenuation coefficient [12].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Mass attenuation coefficient of an element is found to be constant at a particular photon energy, whereas mass attenuation coefficient of a compound or mixture depends upon composition of elements. The linear attenuation coefficient, half-value layer thickness, tenth-value layer thickness and effective atomic number are derived parameters from mass attenuation coefficient [12].…”
Section: Resultsmentioning
confidence: 99%
“…The simulation method for investigation of radiation interaction is found radiologically safer, less time consuming, cost effective and applicable for desired energy of radiation. It is found that Monte Carlo simulation (MCNPX code) is a suitable method for investigation radiation interaction with materials in the literature [12]. The general purpose of MCNPX code is modeling the interaction of gamma rays with matter and tracking all particles at different energies.…”
Section: Introductionmentioning
confidence: 99%
“…As a first step in the INPUT file, cell cards and surface cards were prepared using elemental mass fractions (wt %) and material densities ( Table 1 ) of ZBV1, ZBV2, ZBV3, and ZBV4 glasses in the 0.015–10 MeV photon-energy range. Next, MAC values obtained from WinXcom [ 49 ] and MCNPX [ 50 , 51 , 52 ] were compared. The overall MAC values were largely stable regarding variations in incident photon energy.…”
Section: Methodsmentioning
confidence: 99%
“…0, 0.5, 1, 1.5 mol%) glass system were determined using Phy-X PSD [19] code and MCNPX [20][21][22] Monte Carlo code. Tellur-based glasses usually start to deteriorate and burn at high temperatures (about 900 • C) and accordingly they become a blackish color.…”
Section: Mass Attenuation Coefficients (Macmentioning
confidence: 99%